The Quality Otomation System and monitoring of Bok Choy (Brassica chinensis L.) in Hydroponic Greenhouses based on Fuzzy Logic using Arduino Uno: sistem Otomasi dan Monitoring Kualitas Pakcoy (Brassica chinensis L.) pada Greenhouse Hidroponik berbasis Fuzzy Logic menggunakan Arduino Uno - Radita Febrianti; Ridwan Siskandar; Dwi Yulinar Chairunisa (Universitas Widya Gama Mahakam, 2023)
Hydroponic greenhouses is a form of maintenance optimal plants with minimal water use. However, growing plants in this environment requires careful monitoring and control of various parameters such as pH and nutrient availability. In this study we used NFT Hydroponics (Nutrient Film Technique) a soilless plant cultivation technique that uses nutrient solutions flowing in shallow channels under plant roots. This method allows efficient and optimal plant growth with less use of water and nutrients compared to conventional cultivation. The pakcoy quality monitoring system in this hydroponic greenhouse is made using an Arduino Uno microcontroller equipped with a dfrobot pH sensor and a dfrobot tds sensor to monitor the quality of the bok choy plants automatically. We get the data by the tool will be processed using fuzzy logic to control the pH quality of the water and the nutrients of the bok choy plants to maximize the efficiency and production of the bok choy plants. The results showed that using this technology can monitor and control the water quality and environment for bok choy growth efficiently and accurately.